Antibacterial activity test of papaya peel extract against the growth of S.mutans: Uji aktivitas antibakteri ekstrak kulit pepaya terhadap pertumbuhan S.mutans - Vinsensia Aprilla Ananda Icha; Sinar Yani; Nuryanni Dihin Utami; Yadi; Masyhudi (Makassar Dental Journal, 2023)
Papaya (Carica papaya L.) is a plant where all of it parts can be used. Unripe papaya peel can be used as an herbal ingredient as it is known to have antibacterial effects. The main bacteria that cause dental caries is S.mutans. This study was intended to determine the antibacterial activity of papaya peel extract (PPE) in inhibiting the growth of S.mutans. Laboratory experimental research with posttest only control design, consisting of treatment groups are S.mutans bacteria treated with PPE on disc paper with concentrations of 1%, 10%, 20%, 40%, 60% and 80%, and positive control group is S.mutans bacteria treated with 0.2% chlorhexidine gluconate solution and negative control group is S.mutans treated with aquadest. As a result, PPE has antibact-erial activity against S.mutans. The zone of inhibition was optimal at 40% concentration and decreased at 60% concentration. It was concluded that PPE can inhibit the growth of S.mutans with the largest inhibition zone at 40% concentration.